(untitled) (Research, Society and Development, 2022)
Introduction: this article sought to carry out a literature review regarding the conceptualization of celiac disease and its clinical manifestations, to describe the nutritional therapy recommended by the nutritionist and to verify the psychosocial impacts generated in the life of the celiac patient after diagnosis. Objective: The general objective of the article was to evaluate the nutritional status of patients with celiac disease and the relationship with nutritional therapy in improving quality of life. Methodology: consists of an integrative review, for this review, a search was performed for articles, books, dissertations and theses in the databases SCOPUS, Lilacs, Web of Science, Google Scholar, Scielo, Science Direct, Free Medical Journal, Pubmed/ Medline, CAPES portal journals and a virtual library on health and books. Results and Discussion: Celiac disease is an autoimmune pathology that affects the small intestine of adults and children, caused by the ingestion of foods that contain gluten, that is, a protein present in rye, wheat, oats, barley and malt (by-product of barley). The celiac must always be aware of the nutritional information that make up each food. Conclusion: The treatment of this disease consists of avoiding foods that contain gluten, thus making the role of the nutritionist paramount in terms of adequate nutritional guidance and predisposition to obesity and the development of chronic non-communicable diseases. in adult life.